KELAYAKAN FINANSIAL GULA JAGUNG SEBAGAI BIOINDUSTRI DI KABUPATEN BENGKAYANG - Setyo Utomo, Rudy; Wahyudi, Tri (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2017)
Difficulty of corn farmers for increase their income can be reached by establishing raw materials into finishing product, namely corn sugar. The aim of this study is to find the financial feasibility of processing seed corn into sugar. To determine the feasibility of corn sugar mills conducted a financial feasibility analysis. Financial feasibility analysis results indicate that corn sugar production in Bengkayang feasible on condition Cost of Goods Sold amounted Rp. 84,500.00/Kg. The value of Break Even Point (BEP) 69,387 units, the value of Payback Period (PBP) 2.41, Net Present Value (NPV) Rp.54,592,680,102.46 ,, value Internal Rate of Return (IRR) 25.10%, and the value of Benefit / Cost Ratio (B / C ratio) of 1.35. Investment in corn sugar business still said to be worth doing despite the sensitivity level price down 3% to the sensitivity level of selling prices down 3% and raw materials rose by 4%.